Family farmers' environmental perception of ecosystem services in the Brazilian semi-arid region - Milena Vaz; Hemerson Vitorino; Natacha de Souza; Jéssica da Silva; Denise da Cruz (Journal of Agriculture, Food Systems, and Community Development)
Rural populations, whose economies are based on agriculture and livestock, depend on ecosystem services. The aim of this study was to assess family farmers’ environmental perception of ecosystem services and their importance. The study was conducted in two communities in the semi-arid region of Piauí, Northeastern Brazil. Data were collected through nonparticipant observation and semi-structured interviews and analyzed using word clouds, Likert scales, and semantic networks. Farmers have a broad perception of ecosystem service categories, recognizing and valuing provisioning and cultural services above all. Nature is seen as playing a fundamental role in the activities of these communities, which depend on natural resources for their livelihoods and leisure.